Safe and effective pharmacotherapy in infants and preschool children: importance of formulation aspects. Issue 7 (15th March 2016) - van Riet-Nales, Diana A; Schobben, Alfred F A M; Vromans, Herman; Egberts, Toine C G; Rademaker, Carin M A
Abstract : Safe and effective paediatric pharmacotherapy requires careful evaluation of the type of drug substance, the necessary dose and the age-appropriateness of the formulation. Generally, the younger the child, the more the attention that is required. For decades, there has been a general lack of (authorised) formulations that children are able to and willing to take. Moreover, little was known on the impact of pharmaceutical aspects on the age-appropriateness of a paediatric medicine. As a result of legislative incentives, such knowledge is increasingly becoming available. It has become evident that rapidly dissolving tablets with a diameter of 2 mm (mini-tablets) can be used in preterm neonates and non-rapidly dissolving 2 mm mini-tablets in infants from 6 months of age. In addition, uncoated 4 mm mini-tablets can be used in infants from the age of 1 year. Also, there is some evidence that children prefer mini-tablets over a powder, suspension or syrup. Other novel types of age-appropriate oral formulations such as orodispersible films may further add to the treatment possibilities. This review provides an overview of the current knowledge on oral formulations for infants and preschool children, the advantages and disadvantages of the different types of dosage forms and the age groups by which these can likely be used.